PHOTOSINTETIC PIGMENTS OF Thalassiosira sp AND ITÃâÃâS APLICATION AS AN ACTIVE INGREDIENT OF SUNSCREEN LOTION - PRAJUWITA (NIM: 20514056), MIA
High intensity ultraviolet (UV) radiation exposed to the skin surface may cause skin damage such as sunburn, premature aging and skin cancer. A manner to protect skin from UV radiation exposure is the use of sunscreen lotion. Thalassiosira sp. is a diatom, that can be found in Indonesian waters, produce phothosynthetic pigments such as carotenoids and chlorophyll compunds that are potentially used to protect skin from UV radiation inducing erythema. The aim of the present study is to determine the value of sun protection factor (SPF) of sunscreen lotion supplemented with active ingredient of photosynthetic pigments from Thalassiosira sp. The research steps included cultivating Thalassiosira sp. cells in modified seawater medium, harvesting biomass by the centrifugation methos, drying biomass by the freeze-drying method, extracting photosynthetic pigments using acetone as a solvent, purifiying the photosynthetic pigments by the method of column chromatography eluted by hexane:acetone with a stepwise gradient consentration of 4:1, 3:2, 2:3, and 1:4, characterizing photosynthetic pigments by UV-Vis spectrophotometer and thin layer chromatography (TLC), applying the photosynthetic pigments as active ingredients in sunscreen lotion, on determining SPF value of the sunscreen lotion on New Zealand-albino-rabbit strain in vivo. The results showed that Thalassiosira sp. cells grown in the culture with an initial cell concentration of 2ÃƒÂ—105 cells/mL for 10 d produced wet brownish green pasta biomass of 2.24 Ã‚Â± 0.52 g/L culture. Dried Thalassiosira sp biomass obtained was brownish green powder.Water content of Thalassiosira sp.cells was 90.3%. Total photosyntetic pigments extracted from Thalassiosira sp dry biomass were 0.1185 Ã‚Â± 0.0067 mg/g dried biomass. The photosynthetic pigments in Thalassiosira sp. cells were identified as carotenoids and chlorophyll compounds. The concentration of total carotenoids and chlorophyll a was 46 and 66 mg/mL, respectively. Eight fractions of photosynthetic pigments were identified by TLC each with Rf value of 0.9375, 0.5625, 0.375, 0.3312, 0.2625, 0.2187, 0.1625, and 0.0125. Purified photosynthetic pigments obtained column chromatography were β-carotene (427, 452, and 479 nm), feofitin a (409 and 666 nm), diadinochrome (408.5, 430, and 456 nm), fucoxhantin (447 and 470.5 nm) and chlorophyll c (448 nm). Sunscreen lotion containing 0.2% w/w fucoxanthin was orange with a pH of 6 that suitable for the skin. Irritation tests showed that no erythema and edema were observed on the skin of rabbit tests covered by sunscreen lotion supplemented with active ingredient of fucoxhantin The SPF value of the sunscreen lotion was 1.43 that could absorb 30% UVB radiation. Thus, fucoxanthin from Thalassiosira sp. might be used as an active ingredient of sunscreen lotion.